Oxidative stability of sunflower oils supplemented with kenaf seeds extract, roselle seeds extract and roselle extract, respectively under accelerated storage - Nyam, Kar Lin; Wong, M. M.; Long, Kamariah; Tan, Chin Ping (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
With the concern of adverse effects of lipid oxidation on food deterioration and human health, the antioxidant activities of kenaf seed extracts (KSE), roselle seed extracts (RSE) and roselle extracts (RE) were evaluated by comparing its oxidative stability in refined, bleached & deodorised (RBD) sunflower oils with that of in synthetic antioxidant, BHA. Established methods such as peroxide values (PV), p-anisidine values (AV), TOTOX values, free fatty acids (FFA), iodine values (IV), total phenolic contents (TPC), conjugated dienes (CD) and conjugated triene (CT) were employed to assess the extent of oil deterioration. During 24 days storage, consensus was accomplished based on the results assessed by PV, TOTOX, CD, CT, IV and TPC at which the antioxidant activities of KSE, RSE and RE were better than BHA. Surprisingly, the results obtained by AV and FFA assays showed the reversed. Among the extracts, RSE exhibited the best antioxidant activities. These suggest that KSE, RSE and RE may be used as potential source of natural antioxidants in the application of food industry to prevent lipid oxidation.